Research in University Teaching of Chemistry: A Case in the Faculty’s Initial Teaching - Siso-Pavón, Zenahir (2018)
With the purpose of characterizing the research processes promoted in the university teaching of Chemistry in the initial training of the teaching staff of this discipline, the participant observation was made of the classes of courses taught by four teachers of the area of Organic Chemistry of a Venezuelan university. Categories of analysis and interpretation emerged, which were researched through a retrospective interview; also, a semi-structured interview was applied to twelve students of these courses. The resulting categories were (a) Research as a process, (b) Proposal of problematic situations, and (c) Qualitative study of problem situations, studying the concept of teacher research and its application in teaching practice, consideration of ideas, skills, and attitudes; the use of bibliography, the issuance of hypotheses; the elaboration of solution strategies, and management of new knowledge. It was found that research is mainly understood as the bibliographic inquiry in relation to topics, which allows theoretical and practical approaches without further elaboration of hypotheses and resolution strategies because they are highly directed work with little contribution to the promotion of scientific skills.